Circumstances unknown - Heckler, Jonellen (London : Headline Book Publishing, 1993)
Refusing to call her husband's drowning an accident, photographer Deena Reuschel uncovers two similar deaths, receives support from two of her husband's childhood friends, and discovers a chilling clue in one of her own pictures.
Keywords: Widows -- Fiction; Detective and mystery fiction